Discussion of the Effect of Alternative Accounting Rules for Nonsubsidiary Investments - Gordon, Myron J. (Journal of Accounting Research, 1966)
Myron J. Gordon, Discussion of the Effect of Alternative Accounting Rules for Nonsubsidiary Investments, Journal of Accounting Research, Vol. 4, Empirical Research in Accounting: Selected Studies 1966 (1966), pp. 220-223